Beyond the Facebook post : a critical analysis of the online public sphere in Singapore. - Su, Dickson Bingxing. (2013)
The influence of social media in shaping public opinion and discourse has been extensively noted but research on how it happens in computer-mediated environments is still relatively under-developed. Noting also that credibility perception can often influence discourse and vice versa, the paper attempts to study the subject on social media as a means of strengthening the online public sphere from a Singapore perspective. Where research on social media has largely focused on blogs and their emanating comments, this research focuses on how critical arguments on local Facebook mainstream and alternative news sites develop—including an analysis of comments, which have not been examined in detail in the literature. Furthermore, Facebook allows users to share and like content, which serve as additional indicators for a richer discourse analysis.